Microencapsulação de óleo de chia (Salvia hispanica) para aplicação em queijos processados - Cardoso, Luana Garbin (2019)
The growing demand for functional foods, which in addition to its nutritional function provides consumer health benefits, has prompted the food industry to reshape its products to meet this need. The dairy industries are an important vehicle for functional foods, as these products are well accepted by consumers as food added with healthy compounds. Grana Padano cheese is a dairy product that has a good nutritional composition, but has a high fat content, which is mainly composed of saturated fatty acids. Processed cheeses are products obtained through the fusion of cheeses with the addition of non-dairy products in up to 30%, which allows the addition of functional compounds such as inulin that provides prebiotic effect in the body and chia oil that has high content of unsaturated fatty acids, which are unstable to environmental factors such as light, temperature and oxygen, which generates the need for the oil to be pre-microencapsulated to remain stable in food products. Therefore, it was aimed to contribute to the development of functional foods. The work was divided into 2 stages. In the first stage the chia oil composition was evaluated, and its microencapsulation and microcapsule characterization were performed. In the second step, four processed cheese formulations were formulated: standard formulation (FP), formulation with inulin addition (IF), inulin addition formulation and chia oil microcapsules (FIOCM) and the addition formulation of inulin and chia oil (FIOCL). The processed cheese formulations were characterized by microbiological, physico-chemical and sensorial analyzes. Chia oil had a high content of unsaturated fatty acids. The microencapsulation of chia oil by the ionic gelling technique using sodium alginate and calcium chloride resulted in microcapsules withmicroencapsulation efficiency of 94.37% in the ratio 3: 1 oil: alginate low solubility in water (0 , 04%) and particle size of the microspheres of 195.2 μm, these results being satisfactory because the encapsulation efficiency was considered high, the solubility was low, being ideal for additionof microspheres in food products with high water content and particle size as microspheres. The moisture and fat contents in the dried extract of the formulations obtained are in accordance with the Brazilian legislation. The formulation with inulin addition (IF) showed a 36% fat reduction, the sensorial tests indicated that it did not present a significant difference (p> 0.05) compared to the standard formulation in relation to all attributes analyzed, and presented characteristics similar to the standard formulation, and a functional processed cheese with fat reduction could be produced. The FIOCM showed a significant difference in relation to FIOCL in relation to the taste, proving that the microencapsulation process was able to mask the oil taste, however adjustments in the process are necessary to avoid the formation of agglomerates of microcapsules that interfere in the texture of the product, considering that chia oil adds functionality to it.